Alveolar Osteitis: A Comprehensive Review of Concepts and Controversies - Antonia Kolokythas; Eliza Olech; Michael Miloro (Hindawi Limited, 2010)
Alveolar osteitis, "dry socket", remains amongst the most commonly encountered complications following extraction of teeth by general dentists and specialists. A great body of literature is devoted to alveolar osteitis addressing the etiology and pathophysiology of this condition. In addition numerous studies are available discussing methods and techniques to prevent this condition. To this date though great controversy still exists regarding the appropriate terminology used for this condition as well as the actual etiology, pathophysiology, and best methods of prevention and treatment. This article is a comprehensive critical review of the available literature addressing the concepts and controversies surrounding alveolar osteitis. We aim to assist the dental health care professional with patient preparation and management of this commonly encountered postoperative condition should be encountered.